Antioksidan in vivo buah beligo (Benincasa hispida (Thunb.) Cogn.) berdasarkan penurunan kadar malondialdehid tikus jantan wistar - Alim, Nur; Irfayanti, Nur Alfiah; Fajrianti, Siti; Suarni, Suarni; Jannah, Raudatul (Sasambo Journal of Pharmacy, 2024)
The aim is to ascertain the in vivo antioxidant activity of beligo fruit flesh ethanol extract based on the measurement of malondialdehyde levels in Wistar male rats generated by used frying oil. The procedure involves macerating 70% ethanol to extract the flesh from beligo fruit and assessing the in vivo antioxidant activity by measuring the amounts of malondialdehyde in fifty Wistar male rats split into 5 groups. Group V received vitamin C at a dose of 27 mg/kgBW, and groups II, III, and IV received an ethanol extract of beligo fruit flesh at 100, 200, and 400 mg/kg BW. Group I received 1% Na-CMC as a negative control. Using a UV-Vis spectrophotometer, malondialdehyde levels were determined using the TBARS test. Statistical data analysis by a Completely Randomized Design (CRD) and an Honestly Significant Difference (HSD) follow-up test. Malondialdehyde levels decreased in Group I (19.16%), Group II (78.70%), Group III (82.86%), Group IV (87.76%), and Group V (90.23%) according to the study's findings. The study findings demonstrated the antioxidant potential of beligo fruit flesh ethanol extract at doses of 100 mg, 200 mg/kg BW (p<0.05), and 400 mg/kg BW (p<0.01) in lowering malondialdehyde levels in Wistar male rats.